How time matters to the market - Kahn, Michael N. (FT Press Delivers elements., 2010)
"This Element is an excerpt from Technical analysis plain and simple: charting the markets in your language (ISBN: 9780137042012) by Michael N. Kahn. Understanding time: one of the most crucial, powerful, and underutilized aspects of technical analysis. Time is one of the more underutilized facets of technical analysis. How much time did the market spend in its trend? Is the small trading range now long enough to allow for the excesses and imbalances built up during the trend to dissipate? The concepts of overbought and oversold center around markets that move too far, too fast, and that last term is completely time dependent"--Resource description page.